The particle size effect of CeO2 on the structure and properties of MgAl2O4 spinel ceramics; Ceramics International; Vol. 51, iss. 1 - Paygin V. D. Vladimir Denisovich; Dvilis E. S. Edgar Sergeevich; Stepanov S. A. Sergey Aleksandrovich; Valiev D. T. Damir Talgatovich; Khasanov O. L. Oleg Leonidovich; Deulina D. E. Darjya Evgenjevna; Shevchenko I. N. Ivan Nikolaevich; Huang Fuli (2025, 2025)
Title screen